Aplikasi Pengendalian Persediaan Barang Berbasis Android dengan Metode Economic Order Quantity (EOQ) pada Bengkel Dunia Motor - Leidiyana, Henny; Anugrah, Arya (Jurnal Komtika (Komputasi dan Informatika), 2020)
Good inventory control is something that must be considered in inventory management. The world of motorbikes is a special Honda motorcycle workshop which has a problem, namely a large supply of slow moving parts while a shortage of fast moving supplies. Employees in the spare parts department are also often confused in picking up parts from the warehouse because of unclear inventory information. As a solution, an application is made that applies an optimal inventory of goods using Economic Order Quantity (EOQ), which is a method used to determine the most economical amount of purchases made every time a purchase. Using services from Firebase will simplify the application development process. Because the application is general in nature, for more specific use by considering the characteristics, type and size of the goods, the application can be developed.